(3GdJCKjQGJ GdCaQjbjI Ydi KbGaI eLJeY SGhHGhdh HGdHQGRjd (B: s (3OQGSI ejOGfjI ai GdGfKQhHhdhLjI GdKbGajI (B/ s - (3GjeGf YHOGdJhGH Pci YeGQI s; (3SYO HQcI (B: s; (3Sdhi jhSa OQhjT (B: s ((3GdbGgQI (B: s (3GjeGf YHOGdJhGH Pci YeGQI (B: s, 2016)
(3jJfGhd ehVhY GdOQGSI JGKjQ GdKbGaI GdGaQjbjI Ydi KbGaI eLJeY SGhHGhdh HGdHQGRjd hge eLehYGJ QMdJ Gdi GdHQGRjd cQbjb Ydi jO GdHQJZGdjjf ai GdbQf GdSGOS YTQ MjK GSJbQhG ai hdGjGJ eNJdaI HGdHQGRjd GdJi jHdZ eSGMJgG GcKQ ef KeGfjI edjhf ce eQHY hJYOdGjI SGh HGhdh hGMOI ef GdhdGjGJ GdUfGYjI GdgGeI GdJi jbWf HgG GdcKjQ ef GdGaGQbI GdPjf GKQJ KbGaJge Ydi gPG GdeLJeY hJCKQJ Hg hfJL Yf Pdc GMOi GdKbGaGJ GdgGeI GdJi jWdb YdjgG GdKbGaI GdGaQhHQGRjdjI hGdJi JYO JGKjQ eJHGOd Hjf GdKbGaI GdGaGQbI hKbGaGJ eLJeY SGhHGhdh HGdHQGRjd hdbO Je OQGSJgeG ejOGfjG cfehPL dgPI GdKbGaIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3eYgO GdHMhK hGdOQGSGJ GdGaQjbjI (B- (3bSe GdGfKQhHhdhLjGs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdHQGRjd s; (3GdKbGaI GdGaQjbjI s; (3KbGaI eLJeY SGhHGhdh s